Device-measured physical activity and type 2 diabetes mellitus risk - Li, Wenzhao; Zhang, Weizhi; Xing, Zhenhua (Frontiers in Endocrinology, 2023)
Objectives: We investigated how device-measured PA volume (PA energy expenditure [PAEE]) and intensity (fraction of PAEE from moderate to vigorous PA [FMVPAEE]) were associated with type 2 diabetes mellites(T2DM) incidence.Methods: This was a population-based prospective cohort study including 90,044 participants. The primary exposures were PAEE and FMVPAEE. The secondary exposures were energy expenditure exerted during LPA, MPA, and VPA and their fraction of PAEE.Results: Each 1-SD increase in PAEE was associated with a 17% lower risk of T2DM (HR: 0.83, 95%CI: 0.78-0.98). Each 1-SD increase in FMVPAEE was associated with a 21% lower incidence of T2DM (HR: 0.79, 95%CI: 0.74-0.83). Achieving the same PA volumes (1 KJ/Kg/d) through VPA (HR: 0.88, 95%CI: 0.85-0.91) was more effective in reducing T2DM, followed by MPA (HR: 0.97, 95%CI: 0.96-0.98) and LPA (HR: 0.99, 95%CI: 0.98-1.00). Conclusion: Higher PA volume is associated with a lower T2DM incidence. Achieving the same PA volumes through higher-intensity PA is more effective in reducing T2DM incidence than lower-intensity PA.